Experiences of Novice Iraqi Nurses in Psychiatric Hospitals: A Qualitative Study - Firas Kanawy Al-Aboudy; Hasan Alwan Baiee (Medical Journal of Babylon)
Background: The environment in which novice nurses are required to function may be unfamiliar to them or perhaps completely unfamiliar if they as mental patients. It is important to address and fully comprehend the core of this unusual circumstance for all nursing personnel, particularly new nurses. Objectives: The aim of this study was to investigate and shed light on the experiences of newly graduated nurses who were employed in a mental unit in an Iraqi setting. Materials and Methods: This study was chosen to use descriptive phenomenology. Participants with nursing diplomas and bachelor’s degrees were carefully recruited for this study, and prior to the study, each of them had fewer than 12 months of experience working in mental wards. The Rashad Hospital in Iraq served as the location for the research project. Interviews with individuals conducted in-depth and semi-structure framework was used to acquire the data, which was then evaluated using the Colaizzi technique and Husserlian phenomenology. Results: 19 nurses who have undergone this study, majority of them were female 73.6%, this study uncovered three main themes: I have attempted to transfer to another hospital, Reality differs from theory, and A workplace has gains. Conclusion: This study may provide insight into the lived experiences of beginning nurses working in mental wards, which allowed for the identification of problem areas that need improvement.